Evaluasi Performa Produksi Dan Electrical Submersible Pump (Esp) Terpasang Pada Sumur X Di Lapangan Y - Mitha Tambunan; Diyah Rosiani; Kristofol Waas (Journal Mechanical Engineering, 2023)
Well X is one of the oil wells located in field Y that has been producing using artificial lift. Well X has changed the artificial lift from SRP to ESP to optimize the well production rate due to a decrease in production. Electrical submersible pump is a multistage centrifugal pump with several impellers and diffusers at each stage. The current pump data uses 21 stages and a frequency of 45 Hz with an oil production rate of 7.1 bopd and a water cut of 99%. The well production capacity known by using IPR is 4542.436 bfpd. From the production history data, the author calculates the remaining reserves that can be produced until the q-limit with the Decline Curve Analysis (DCA) method. Next, an evaluation of the installed ESP pump is conducted using the pipesim simulator. This evaluation involves nodal analysis and sensitivity testing to assess the pump performance and optimize the flowrate production. The analysis results show the remaining reserves that can be produced are 2043 MSTB. Sensitivity tests on tubing size, stages, and frequency indicated that the pump operates optimally with a tubing size of 2.992 inches, 21 stages, and a frequency of 45 Hz, resulting in a production rate of 3503.85 STB/d at a pressure of 88.86 psi. The research result show that the ESP pump operates optimally, and the use of ESP has been proven to increase the production rate from 3133,4 STB/d to 3503,85 STB/d.  Keywords : DCA, ESP, nodal analysis, optimum production